Health of the Nation: the Impact of Racial and Income Segregation on Food Insecurity in the United States - (:unkn) unknown (My University, 2015)
One in six Americans experience food insecurity as a result of not being able to consistently obtain the food they need. Food insecurity ranges from not being able to afford balanced meals to the skipping meals as a way to stretch food budgets. Food insecurity impacts many people in the United States, but it disproportionately impacts people of color and those living in poverty. Racial and income segregation may act to concentrate food insecurity in a few geographic areas with high concentrations of minority and/or poor residents. This is an issue of major concern because studies have shown that racial segregation is a strong predictor of differences in mortality and other health outcomes when looking at black-white and Hispanic-white segregation. While this research has shown a strong link between segregation and these health outcomes, no research has been done on racial and income segregation effects on food insecurity in the United States. This study used nationally representative datasets with information from multiple geographic levels to assess the connection between racial and income segregation and household and child food insecurity. For residential segregation by race, the results showed that (1) black-white segregation was not significantly associated with food insecurity rates and that (2) higher levels of Hispanic-white segregation were associated with increased rates of overall and child food insecurity, but only in counties with relatively large U.S.-born Hispanic populations. The results also showed that three dimensions of income segregation (the segregation of affluence, the segregation of poverty and overall income segregation) were generally associated with higher levels of overall and child food insecurity, especially in counties with relatively high proportions of poor children and relatively small affluent populations. However, poverty segregation was associated with lower rates of child food insecurity, especially in counties with relatively high child poverty rates. These results suggest that residential segregation by race and income are key factors that contribute to food insecurity rates nationally. This research contributes to the public health literature on how residential segregation impacts health outcomes and conditions by extending this line of research to include food insecurity.
Keywords: Food Insecurity; Income Segregation; Residential Segregation; Urban Inequality